CRIMINAL-LEGAL PROTECTION OF THE PUBLIC MORALS IN WESTERN COUNTRIES - A. E. Shalagin (Russian Journal of Economics and Law)
The article views the crimes against public morals in foreign legislation. Special attention is paid to the crimes connected with prostitution, pornography circulation, destruction and damage of historical and cultural monuments, desecration of the graves, and cruelty to animals.